Pre-engraftment neurological impairment in allogeneic stem cell transplant: A case report of atypical posterior reversible encephalopathy syndrome with pontine involvement - Acerbis, Andrea; Orofino, Giorgio; Campodonico, Edoardo; Del Poggio, Anna; Xue, Elisabetta; di Matteo, Francesca; Spelta, Greta; Bruno, Alessandro; Falini, Andrea; Ciceri, Fabio; Peccatori, Jacopo; Greco, Raffaella (Frontiers in Transplantation, 2023)
In the present report, we describe the case of a 59-year-old female who developed pre-engraftment multiple organ failure (MOF) after allogeneic hematopoietic stem cell transplant (HSCT), followed a few days later by a cohort of neurological symptoms leading to a diagnosis of posterior reversible encephalopathy syndrome (PRES). The diagnosis was achieved by excluding more frequent entities associated with neurological symptoms in HSCT and supported by compatible magnetic resonance imaging (MRI) findings, with remarkably interesting less frequent pontine involvement. GvHD prophylaxis, including sirolimus and mycophenolate mophetil (MMF), was discontinued, while carefully controlling blood pressure. In addition, high dose steroids were employed. After 2 weeks, the neurological symptoms abated, and follow-up MRI showed complete regression of neurological alterations, confirming the diagnostic hypothesis of PRES.